Biofortification of Three Cultivated Mushroom Species with Three Iron Salts-Potential for a New Iron-Rich Superfood - Budzyńska, Sylwia; Siwulski, Marek; Gąsecka, Monika; Magdziak, Zuzanna; Kalač, Pavel; Niedzielski, Przemysław; Mleczek, Mirosław (Molecules (Basel, Switzerland), 2022)
Mushrooms fortified with iron (Fe) can offer a promising alternative to counter the worldwide deficiency problem. However, the factors that may influence the efficiency of fortification have not yet been fully investigated. The aim of this study was to compare the effects of three Fe forms (FeCl3 6H2O, FeSO4 7H2O, or FeHBED) in three concentrations (5, 10, or 50 mM) for three mushroom species (Pleurotus eryngii, P. ostreatus, or Pholiota nameko) on their chemical composition, phenolic compounds, and organic acid production. The most effective metal accumulation of all the investigated species was for the 50 mM addition. FeCl3 6H2O was the most favorable additive for P. eryngii and P. nameko (up to 145 and 185% Fe more than in the control, respectively) and FeHBED for P. ostreatus (up to 108% Fe more than in control). Additionally, P. nameko showed the highest Fe accumulation among studied species (89.2 ± 7.51 mg kg-1 DW). The creation of phenolic acids was generally inhibited by Fe salt supplementation. However, an increasing effect on phenolic acid concentration was observed for P. ostreatus cultivated at 5 mM FeCl3 6H2O and for P. eryngii cultivated at 5 mM FeCl3 6H2O and 5 mM FeSO4 7H2O. In the case of organic acids, a similar situation was observed. For P. ostreatus, FeSO4 7H2O and FeHBED salts increased the formation of the determined organic acids in fruiting bodies. P. eryngii and P. nameko were characterized by a much lower content of organic acids in the systems supplemented with Fe. Based on the obtained results, we recommend starting fortification by preliminarily indicating which form of the element is preferred for the species of interest for supplementation. It also seems that using an additive concentration of 50 mM or higher is most effective.
Keywords: phenolic acids; Pholiota nameko; supplementation; Biofortification; Pleurotus; Pleurotus ostreatus; malnutrition; Salts; biofortifikace; soli; organic acids; Iron; Pleurotus eryngii; železo; Agaricus; functional food; deficiency